2010
DOI: 10.1111/j.1469-8137.2009.03163.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hypernodulation in soybean by a leaf‐extracted, NARK‐ and Nod factor‐dependent, low molecular mass fraction

Abstract: Summary• Legumes regulate the number of nodules they form via a process called autoregulation of nodulation (AON). This involves a shoot-derived inhibitor (SDI) molecule that is synthesized in the shoots and is transported down to the roots where it inhibits further nodule development.• To characterize SDI, we developed a novel feeding bioassay. This involved feeding aqueous leaf extracts directly into the petiole of hypernodulating and supernodulating nark mutant plants of Glycine max (soybean). These mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 66 publications
4
74
0
Order By: Relevance
“…These findings support the hypothesis that the systems that autoregulate nodulation are responsible for the shifts seen in the community of symbiotic bacteria here and in previous studies (21), because, under the field conditions examined, autoregulation was activated only in the wildtype Enrei. Furthermore, leaf tissue is currently believed to be the site of production of SDF, which suppresses rhizobial infection of roots (26,34,47). Therefore, the effects of SDF could be reflected more directly in the community structures of leaf-associated bacteria than in those of stem-associated bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support the hypothesis that the systems that autoregulate nodulation are responsible for the shifts seen in the community of symbiotic bacteria here and in previous studies (21), because, under the field conditions examined, autoregulation was activated only in the wildtype Enrei. Furthermore, leaf tissue is currently believed to be the site of production of SDF, which suppresses rhizobial infection of roots (26,34,47). Therefore, the effects of SDF could be reflected more directly in the community structures of leaf-associated bacteria than in those of stem-associated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These findings led to the question of whether soybean-asso-ciated bacteria are more tightly regulated in leaves than in stems, since the shoot-derived factor (SDF) for the autoregulation of nodulation is thought to be produced there (26,47). If this is the case, then the observation of more direct and clear effects of autoregulation systems on soybean-associated bacteria, including endophytes and epiphytes, could be expected in the leaves than in the stems.…”
mentioning
confidence: 99%
“…This perception results in the production of a shootderived inhibitor (SDI), which travels to the roots to inhibit further nodule development (Delves et al, 1986;Lin et al, 2010;Sasaki et al, 2014). Excitingly, recent evidence has revealed that cytokinins, whose production is activated by Lj-HAR1 perception of AON CLE peptides in the shoot, may function as an SDI to systemically suppress nodulation in L. japonicus (Sasaki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Grafting experiments have shown that HAR1 and its orthologs function in the shoot to control root nodule number. Thus, HAR1 is likely to be involved, directly or indirectly, in the generation of a shoot-derived mobile signal that inhibits further nodulation (Krusell et al, 2002;Nishimura et al, 2002;Jiang and Gresshoff, 2002;Buzas and Gresshoff, 2007;Lin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%